2018
DOI: 10.1016/j.heliyon.2018.e00526
|View full text |Cite
|
Sign up to set email alerts
|

ReHabgame: A non-immersive virtual reality rehabilitation system with applications in neuroscience

Abstract: This paper proposes the use of a non-immersive virtual reality rehabilitation system “ReHabgame” developed using Microsoft Kinect™ and the Thalmic™ Labs Myo gesture control armband. The ReHabgame was developed based on two third-person video games that provide a feasible possibility of assessing postural control and functional reach tests. It accurately quantifies specific postural control mechanisms including timed standing balance, functional reach tests using real-time anatomical landmark orientation, joint… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…An expanding number of analysts focus on portraying the estimation of rehabilitation intercessions that can be utilized all through the disease, from the underlying side effects to the propelled stages [4]. Our previous research [5], [6] have also shown that integrating off-the-shelf devices with video game rehabilitation program could facilitate a platform to enable…”
Section: Introductionmentioning
confidence: 99%
“…An expanding number of analysts focus on portraying the estimation of rehabilitation intercessions that can be utilized all through the disease, from the underlying side effects to the propelled stages [4]. Our previous research [5], [6] have also shown that integrating off-the-shelf devices with video game rehabilitation program could facilitate a platform to enable…”
Section: Introductionmentioning
confidence: 99%
“…Stets et al (2017) work with a point cloud from Microsoft Kinect. Esfahlani et al (2018) reported on non-immersive VR in rehab. Uppot et al (2019) describe VR and AR for radiology.…”
Section: Virtual Reality In Medical Researchmentioning
confidence: 99%
“…Electromyography (EMG) can be used for analyzing the degree of muscular activity when performing different VR exercises [ 51 ] or the use of myoelectric signals for controlling prosthetics [ 52 ]. VR rehabilitation game examples include the use of Microsoft Kinect and Myo gesture control armband (with EMG integrated) for treating people with neurological disorders [ 53 ]. Regarding EEG monitoring, this helps studying the effects of VR training over neural reorganization and can be used as a facilitator for a brain–computer interface (BCI) [ 54 ].…”
Section: Ict Solutions For Neurological Disorders Treatmentmentioning
confidence: 99%